2010
DOI: 10.3109/09637481003757860
|View full text |Cite
|
Sign up to set email alerts
|

Dietary total antioxidant capacity and obesity in children and adolescents

Abstract: Dietary antioxidant intake has been suggested to protect against oxidative damage and related clinical complications. The aim of this study was to assess the potential relationships between the dietary total antioxidant capacity (TAC) and obesity-related features in children and adolescents. Anthropometric variables from 369 children and adolescents were measured (184 obese and 185 control). A validated food-frequency questionnaire was used to calculate the TAC and the daily nutrient and energy intake. Dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 34 publications
(35 reference statements)
2
46
0
3
Order By: Relevance
“…Studies to determine the association between increasing F & V intake and losing body fat among children possibly is still under examination by others. Similar results revealed that waist circumference [73], hip circumference, WHtR and WHR [66] were all negatively associated with increased F & V intake. These effects were not previously reported in studies where these parameters were measured for example in young women aged 18 -28 years [74] or in preschool children 3-6 years old [69].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Studies to determine the association between increasing F & V intake and losing body fat among children possibly is still under examination by others. Similar results revealed that waist circumference [73], hip circumference, WHtR and WHR [66] were all negatively associated with increased F & V intake. These effects were not previously reported in studies where these parameters were measured for example in young women aged 18 -28 years [74] or in preschool children 3-6 years old [69].…”
Section: Discussionsupporting
confidence: 73%
“…people living in deprived areas and on low income), as similar findings were previously reported in qualitative studies among adults [60], British young adults age 18-24 years old [61], among both children and adults [62], and quantitative studies of Portuguese high school students [63]. These determinants were: cost, lack of young-middle and older adults [64] [65] and children (7 and 15 years old) [66].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In a similar way, Bahadoran et al (2012), showed that a higher intake of dietary antioxidants also resulted in lower body weight and abdominal fat gain in adults [2]. Moreover, showed an inverse association between adiposity (BMI-SDS, total body fat) and dietary TAC in obese children [36]. It seems that the potential effects of food antioxidants may occur through modification of lipids and carbohydrates metabolism, increased insulin sensitivity, and regulation of both appetite and adipocytokines [26].…”
mentioning
confidence: 82%
“…The results obtained for both types of extracts (aqueous and methanolic) reveal the antioxidant capacity of rama tomato, a reflex of the content in bioactive compounds (with different polarities) able to prevent oxidation via complementary mechanisms. Tomato intake is, therefore, a way of increasing total dietary antioxidant capacity, which has been recently described as a potential indicator of the risk to develop obesity-related features (Puchau et al, 2010). The anthropometric and biochemical characterization of the young women enrolled in the study, before and after 4 weeks of pre-meal rama tomato ingestion, is presented in Table 3 and the results of the statistical treatment of the data are presented in Figure 2 and Table 4.…”
Section: Resultsmentioning
confidence: 99%